Studi E-Learning Berbasis Knowledge Management Lingkungan Hidup - Prasetya Cahya Saputra; Wahyu Sardjono; Tri Pudjadi (ComTech: Computer, Mathematics and Engineering Applications, 2013)
National sustainable development needs to take into account the utilization of environmental natural resources for future generations. For the community, environment is a space or a place to stay for that need to be more preserved than utilized. Collaboration between knowledge of environment and preservation with ICT knowledge can be developed into a management system which is environmental knowledge management systems. Approach on the efficiency and effectiveness of ICT, which include variable timing, capacity, relevance,accessibility, flexibility, accuracy and reliability, can be used to explore the success determinants of communitybased environmental conservation as a central participant. Analysis method of this study uses the Core Processof KM consisting knowledge identification, knowledge aqcuition, knowledge development, knowledge sharing and distribution, knowledge utilization, and knowledge retention. Menawhile, the design method uses objectorientedbased approach (OOAD) that contains the UML diagrams, followed by evaluation and verification of test results of the e-learning application prototype which will be measured by IT Balanced Scorecard through four perspectives, namely: (1) government contribution; (2) society orientation, (3) excellent operation, (4)future orientation. With the formulation of the critical success factors is then developed a virtual learning model, in order to raise public awareness of the importance of environmental preservation. The result is a prototype model of environmental KMS application or e-learning which will be piloted in a few areas, especially in Jabodetabek.